Sanatoriul – spaţiu al erosului şi al thanatosului în romanul lui Max Blecher - Anamaria Ciobotaru (Revista de Istorie și Teorie Literară)
The present approach is based on the idea that, with Blecher, Eros is developed between two limits, evolving from pleasant sensations to resentments. The attitude the character has towards love is in fact a reaction to the disease he is consumed by. Certainly, the ailment involuntarily dominates all the character’s feelings and he cannot think or feel outside the limits imposed by the disease. The sanatorium functions as a drug that insinuates itself slowly and permanently onto the characters. Once you enter this space there is something that prevents you from leaving it. The behaviour becomes automated, the reactions are predictable, the coordinates according to which life unfolds are Eros – Thanatos. The ailment is the common point for everyone. Each character lives a love story, each being destined to die in a certain way. The novel speaks about the stories of those trying to escape this space without having regrets, an almost impossible fact.